Understanding variability in algal solid-liquid separation process outcomes by manipulating extracellular protein-carbohydrate interactions - Rao, N.R.H.; Granville, A.M.; Henderson, R.K. (Water research (Oxford), 2021)
•HMW and high charge proteins and carbohydrates can enhance algal separation•Several types of protein-carbohydrate interactions influence separation•Algal separation is low if protein-carbohydrate-cell-polymer networks do not form Coagulation-flocculation followed by sedimentation or dissolved air flotation (DAF) are processes routinely used for separating microalgae from water; however, during algae separation then can exhibit inconsistent separation, high coagulant demand, and high operating cost. To circumvent these problems, previous studies reported the development of a novel DAF process in which bubbles were modified instead of particles. While this process was shown to be sustainable and inexpensive, the problem of inconsistent algal separation across species remained. Recent research has suggested that this could be due to the varying concentration and character of algal-derived proteins and carbohydrates within the extracellular organic matter (EOM) and their associated interactions. This hypothesis is tested in the current study using the novel modified-bubble DAF process, which has been highly susceptible to EOM protein and carbohydrate concentrations and character. Biomolecular additives (commercially available proteins and carbohydrates, and algal-extracted proteins) of widely differing molecular weight (MW) and charge were dosed in varying proportions into samples containing either Chlorella vulgaris CS-42/7, Microcystis aeruginosa CS-564/01, or Microcystis aeruginosa CS-555/1 after removing the intrinsic EOM. These cell-rich suspensions were then subject to flotation using cationic bubbles modified with poly(diallyldimethylammonium chloride) (PDADMAC). When additives were dosed independently, separation increased from <5% to up to 62%. The maximum separation was obtained when the dose was double the respective biopolymer concentration measured in the intrinsic EOM for the equivalent species, and, in the case of protein additives, when MW and charge were >50 kDa, and >0.5 meq·g−1, respectively, irrespective of the species tested. When evaluating steric- and charge-based protein-carbohydrate interactions on cell separation by simultaneously dosing high MW and high charge protein- and carbohydrate-additives, enhanced separation of up to 79% was achieved. It is suggested that enhanced cell separation is achieved due to proteins and carbohydrates bridging with cells and forming protein-carbohydrate-cell suprastructures in the presence of a flocculant, e.g. PDADMAC, and this only occurs when the intrinsic EOM comprises proteins and carbohydrates that have high MW (>25 kDa) and charge (>0.2 meq·g−1), and interactions with each other and with the cell surface. [Display omitted]